A narrative review of antibody–drug conjugates in EGFR-mutated non-small cell lung cancer - Hsu, Robert; Benjamin, David J. (Frontiers in Oncology, 2023)
In the past 15 years, non-small cell lung cancer (NSCLC) treatment has changed with the discovery of mutations and development of new targeted therapies and immune checkpoint inhibitors. Epidermal growth factor receptor (EGFR) was the first mutation in NSCLC to have a drug that was FDA approved in 2013. Osimertinib, a third-generation tyrosine kinase inhibitor, is approved as first-line therapy for advanced NSCLC and in the adjuvant setting for Stage IB-IIIA resected NSCLC. However, resistance to osimertinib is inevitably an issue and thus patterns of resistance to EGFR mutated NSCLC have been studied including MET amplification, EGFR C797X acquired mutation, HER-2 amplification, and transformation to small cell and squamous cell lung cancer. Current management for EGFR mutated NSCLC upon progression of EGFR TKI are limited at this time to chemotherapy, radiation therapy sometimes in combination with continuation of osimertinib. Antibody drug conjugates (ADCs) are made up of a monoclonal antibody linked to a cytotoxic drug, are an increasingly popular class of drug being studied in NSCLC. Trastuzumab deruxtecan has received accelerated FDA approval in HER-2 mutated NSCLC. ADCs offer a possible solution in finding a new treatment that could bypass the intracellular resistance mechanism. In this review article, we summarize of the mechanism of ADCs, investigational ADCs for EGFR mutated NSCLC which include targets to MET amplification, HER3, Trop2, and EGFR along with other ADC targets being investigated in NSCLC and discuss future directions that may arise with ADCs in EGFR mutated NSCLC.